Stosunki białorusko-ukraińskie w kontekście Partnerstwa Wschodniego. Impas czy intensyfikacja współpracy? - Prokop, Maryana; Brin, Pavlo (Historia i Polityka, 2019)
The article contains an analysis of the current aspects related to the Belarus and Ukraine cooperation under the EU Eastern Partnership. The timeframe covers a period of 2009–2012, starting from the 2009 Summit in Prague. It is also important to mention some earlier aspects having a great impact on the discussed issues in the legal, political, and economic context.